English-Medium Instruction and Translanguaging 2021
DOI: 10.21832/9781788927338-013
|View full text |Cite
|
Sign up to set email alerts
|

9 Student Translanguaging Practices in the EMI Classroom: A Study of Italian Higher Education

Abstract: This chapter reports on a study of student translanguaging practices in English-medium instruction (EMI) at an Italian university. Translanguaging is intended here as the strategic use that multilingual speakers make of their entire linguistic repertoire so as to facilitate the effective learning of content. Meanwhile, EMI is defined as the adoption of English to teach academic content in countries where the first language for communication is not English. The data analysed for this chapter have been collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Fluid use of language, as seen in Extracts 4 and 6, for instance, acted as an engagement strategy on the part of the teacher through pedagogical translanguaging, linking the shared language outside the classroom with the classroom, rather than separating the two languages . Similar functions related to the "social side of translanguaging" (Chang, 2019, p. 33) are also reported by Dalziel and Guarda (2021) in their study that views translanguaging practices as opportunities "to enhance the affective atmosphere among speakers and thus create a safe place for everyone to express their ideas" (Dalziel & Guarda, 2021, p. 138) by building personal relations with the students via the shared language outside the classroom.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Fluid use of language, as seen in Extracts 4 and 6, for instance, acted as an engagement strategy on the part of the teacher through pedagogical translanguaging, linking the shared language outside the classroom with the classroom, rather than separating the two languages . Similar functions related to the "social side of translanguaging" (Chang, 2019, p. 33) are also reported by Dalziel and Guarda (2021) in their study that views translanguaging practices as opportunities "to enhance the affective atmosphere among speakers and thus create a safe place for everyone to express their ideas" (Dalziel & Guarda, 2021, p. 138) by building personal relations with the students via the shared language outside the classroom.…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, these fluid language use practices serve as negotiation of meaning, discussion of content, reflection, and leveraging linguistic repertoires. Other studies also reported such observations that examined translanguaging in EMI contexts (e.g., Dalziel & Guarda, 2021;Sobkowiak, 2022). Translanguaging practices functioned as scaffolding, as seen in Extract 5, as the students engaged in meaning-making processes where Turkish helped the student retrieve lexical items in English.…”
Section: Discussionmentioning
confidence: 84%
“…Through analyses of classroom discourse among teachers, different translanguaging strategies emerged [31,34,47] and specific pedagogical purposes such as bridging outside knowledge and colearning were highlighted [14,49]. Even the limited number of studies that did prioritize student contributions in classroom interactions showed more interest in categorizing students' translanguaging practices according to classroom activities [41,58]. The present study aimed to understand the translanguaging practices of students from the viewpoint of their motivations instead of emphasizing pedagogical functions in micro-teaching contexts.…”
Section: Discussionmentioning
confidence: 96%
“…This inclusion of the students’ first language can be considered a form of translanguaging, in which learners’ (and instructors) use all available linguistic resources available to them in order to make sense of and learn new content. From a translanguaging perspective, use of the students’ multiple languages is seen not as limiting or constraining English-medium instruction, but as offering a number of affordances, including scaffolding for less proficient students, encouraging transfer of academic skills, engaging students in deeper learning, easing task management, and strengthening student cooperation (Adamson & Fujimoto-Adamson, 2021; Dalziel & Guarda, 2021; Goodman et al, 2021; Luckett & Hurst-Harosh, 2021).…”
Section: Discussionmentioning
confidence: 99%